Differentiation of two industrial oil sands process-affected waters by two-dimensional gas chromatography/mass spectrometry of diamondoid acid profiles - Rowland, S.; West, C.; Scarlett, Alan; Ho, C.; Jones, D. (2012)
RATIONALE Processing of the oil sands of Canada has produced large amounts of process-affected water (OSPW). Concerns have been raised over the possible environmental impacts of any leakage of OSPW from storage lagoons which contain toxicants, including organic acids. Natural weathering of oil sands deposits may also produce the toxicants, including the acids. Therefore, there is a need for differentiation of the possible natural and industrial sources of such toxicants and also for methods suitable for monitoring changes in the composition of OSPW during long-term storage. METHODS Here we show in a simple preliminary study of the two samples currently available to us, by use of comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (GCxGC/ToF-MS), the distributions of methyl esters of individual isomeric diamondoid acids in OSPW from lagoons with different histories and from different industrial operators. RESULTS We show that the distributions of methyl esters of individual isomeric diamondoid acids, including methyladamantane carboxylic and ethanoic acids, identified by comparison with data for reference compounds, can be differentiated readily. The use of acids with known structures, each verified by authentic acids, known toxicities and known and/or predictable physicochemical properties, to distinguish the different sources is advantageous, since factors likely to control the fate and dispersion of the acids can then more easily be predicted. It is postulated that the differences observed in the relative amounts of some of the acids result from variable extents of bacterial transformation of the organic matter in OSPW. CONCLUSIONS The differences in distributions of diamondoid acids clearly vary between the two samples of OSPW and may prove very useful for monitoring the fate of different sources of OSPW both in storage and in the wider environment, once a wider collection of representative samples is available for study. Copyright © 2012 John Wiley & Sons, Ltd.